Accelerating National Policymaking across Sectors to Enhance Nutrition - Mwadime, Robert K. N. (International Food Policy Research Institute, 2012)
National development plans in Africa are increasingly recognizing nutrition as both essential for development and a social right. So far, however, this has not resulted in the large-scale provision of nutrition services necessary to reduce the high levels of malnutrition on the continent. Nutrition now has to feature more prominently in policymaking processes, and the resultant policies have to be translated into effective programs to achieve a significant reduction in the burden that malnutrition imposes on so many African households, communities, and nations. The experience of East Africa has relevance for policy and program design in other regions affected by malnutrition.